PENGARUH PERSONAL BRANDING TASYA DI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PRODUK MOTHER OF PEARL - Tarina, Miftah; Faaroek, Safiani A.; Resman Muharul (FISIP UPNVJ, 2023)
Social media is the result of the development of technological advances. Instagram is one form of social media. Instagram is the right platform to promote a product, one of which is makeup products that are favored by Indonesian women to support their appearance. Local products innovate and promote to introduce their products to the public and compete with global-scale beauty products to take advantage of beauty influencers on Instagram social media so that the promotional reach can be right on target. One of the most influential beauty influencers for consumers is Tasya Farasya. Tasya Farasya is a beauty influencer who is quite well known on Instagram with strong and attractive personal branding, which can be seen from her always glamorous appearance and honesty in conducting product reviews. Tasya Farasya officially launched her beauty brand